Medication-Related Osteonecrosis of the Jaws Initiated by Zoledronic Acid and Potential Pathophysiology - Aya Alsalih; Annica Dam; Pia Lindberg; Anna Truedsson (MDPI AG, 2021)
The aim of this systematic review is to present an up-to-date review of available publications investigating the cellular mechanisms initiating the development of medication-related osteonecrosis of the jaw caused by zoledronic acid. Electronic searches of MEDLINE/PubMed and Scopus were conducted on the 3 June 2019. A total of 804 publications were identified, of which 11 met the inclusion criteria and were, therefore, included in this study. All the included studies were in vitro studies investigating various human cells. The current review found that zoledronic acid in various concentrations increased apoptosis and decreased migration and proliferation of epithelial cells, fibroblasts, osteoblasts, endothelial cells and dental pulp stem cells, which can affect local tissue homeostasis. The consequences of zoledronic acid were found to be both time- and dose-dependent. The pathophysiology of medication-related osteonecrosis of the jaw is likely a multifactorial process involving prolonged wound healing, chronic inflammation and altered bone remodelling following the administration of zoledronic acid. Further research is needed to identify the exact pathophysiology to optimise management and treatment.